Sustainable Development of Enterprises in the Pandemic: Economic Slowdown, Recession and Crises in the World - Jerzy WACHOL (Communications of International Proceedings, 2021)
The study presents changes of the environment in global economy that have an impact on the development of enterprises, taking into account the sustainable development over the recent years as well as the pandemic context. Transmissions of economic effects in the world caused by large corporations are demonstrated. Based on the analysed socioeconomic statistical data, selected aspects of the development of enterprises are shown in the theoretical aspect and in the global environment, taking into consideration ecology and risk. After Great Britain exited from the EU in 2019, the union became economically weaker by nearly 14% and there can be less support funds for distribution among enterprises, at least in terms of the funds not generated on credit in the EU. Based on the collected socioeconomic statistical data as well as surveys and own observations, conclusions were drawn concerning the sustainable development during the pandemic.
Keywords: Development of Enterprises; Sustainable Development; Pandemic; Business Environment; Corporate Supervision; Globalization; Management Methods.